The crustal structure of the southern Davie Ridge offshore northern Mozambique – A wide-angle seismic and potential field study - Vormann, Maren; Franke, Dieter; Jokat, Wilfried (Tectonophysics, 2020)
Some of the oldest surviving oceanic basins in the world, the Mozambique and West Somali basins, were created during the breakup of Gondwana, starting around 180 Ma. Between the two basins, relative movements of West Gondwana and East Gondwana, including Madagascar, created a shear zone, the Davie Fracture Zone (DFZ) with a topographic elevation (Davie Ridge - DR) marking its centre. The crustal composition of the DFZ and DR is a subject of speculation and debate. In this study, we present seismic refraction data across the prominent topography of the southern DR. Ray tracing of the wide-angle data as well as additional seismic amplitude modelling and 2.5D density modelling constrain its crustal structure and architecture. The data indicate that in the Mozambique Channel the DR consists of fragments of continental crust with a thickness of 10 to 12 km. An oceanic crust indenter extends northward from the Mozambique Basin into the area between the DR and the East African margin at 16.5°S. Northeast of the DR, at 41.8°W/14.5°S, the Somali Basin is probably floored by 6 km thick oceanic crust. Hence, the continental DR separates oceanic crust of the Somali and Mozambique basins. The transitional crustal area at the central Mozambican margin is underlain by high velocity lower crust (HVLC). The HVLC has velocities up to 7.3 km/s and extents along the margin, vanishing northward between 16.5° and 14.5°S. At the Madagascan side of the DR, at 16.5°S, the highly intruded stretched continental crust is 9 km thick and possibly underlain with a smaller HVLC of 2.9 km thickness and an E-W extent of 120 km. The oceanic crust at 14.5°S represents the oldest part the Somali Basin, which formed after the initial NW-SE rifting between East and West Gondwana. •We present new seismic refraction data from the Mozambique Channel.•The Davie Ridge separates the oceanic crust of the Somali and Mozambique Basins.•A high velocity lower crust extends along central Mozambique up to 16°S.•The Davie Fracture Zone evolved in a larger area of transtensional deformation.